Irish women's fiction of the twentieth century - Ukić Košta, Vesna (ELOPE (Ljubljana), 2014)
This paper explores the ways in which some of the best and most representative Irish women fiction writers of the twentieth century responded to the exigencies of Catholicism in their selected works. It also attempts to demonstrate how the treatment of Catholicism in Irish women's fiction changed throughout the century. The body of texts that are examined in the paper span almost seventy years, from the early years of the independent Irish state to the turn-of-the-century Ireland, during which time both Irish society and the Irish Catholic Church underwent fundamental changes. How these authors tackle the relationship between the dominant religion and the shaping of woman's identity, how they see the role of woman within the confines of Irish atholicism, and to what extent their novels mirror the period in which they are written are the main issues which lie in the focus of the paper.
Keywords: avtoriteta; Catholicism; cenzura; irska književnost; irske pisateljice; katolištvo; verska ideologija